Co-occurring intimate partner violence, mental health, and substance use problems: a scoping review - Robin Mason; Susan E. O'Rinn (Taylor & Francis Group, 2014)
Background: Intimate partner violence (IPV) is a pervasive, serious problem detrimental to the health of untold numbers of women. In addition to physical injuries that may be sustained, IPV has been significantly associated with mental health challenges including substance use problems. The problems are complex, highly correlated with each other, and bidirectional in nature. Although as many as 50% of women in mental health and between 25% and 50% of women in substance abuse treatment programs report IPV, frontline workers in all three sectors state they lack the training to address these co-occurring problems. Objective: To determine what frontline IPV, mental health, and substance use workers need to know in order to provide appropriate care to women experiencing co-occurring IPV, mental health and/or substance use problems. Design: Using Scholars Portal OVID, Medline and OVID PsycINFO and combinations of significant terms, we conducted a scoping review of articles published between 2005 and 2014. Results: An initial 4017 records were retrieved (3484 from Scholars Portal, 272 from Medline, 261 from PsycINFO). After applying inclusion and exclusion criteria, 35 articles were reviewed. Of these, 14 examined the relationships among IPV, mental health, and substance use; 7 focused on IPV and mental health; 14 looked at IPV and substance use. Conclusions: Although education and training frequently figured among the recommendations in the reviewed articles, specific content for proposed education or training was lacking. The most frequently occurring recommendations focused on the need to develop better collaboration, coordination, and integration across IPV, mental health and addiction treatment services.